Compensation from Civil Liability Arising From Drugs and Vaccine Damages - Rayan Jehad Al-Shamaila (Polit Journal Scientific Journal of Politics, 2022)
This research addresses the issue of compensation from civil liability arising from the damages caused by medicine and vaccines by indicating the types of compensation within the framework of civil liability for damages caused by drugs and vaccines and their applicability to compensation arising from the harm caused by the medicine or vaccine to the patient. This research also included the effect that changing the damage over time has on the amount of compensation. We presented in this paper the aggravation of the damage and the increase in its volume to the injured after a period of time, then talked about the effect that the decrease or elimination of this damage would have on the compensation estimated by the court. We presented the controls for the adoption of these types of compensation by the court when filing a claim for the harm caused by drugs and vaccines, and the position of Jordanian legislation thereon, through the adoption of many texts and several resolutions dealing with the decrease in the amount of compensation, and the decrease in the amount of the issue, which the compensation, However, the Jordanian authorities did not directly mention the issue of the decrease in damage and its impact on compensation. We tried to explain the general controls that should be covered by this decrease, especially the court decisions related to it. The research ended with a conclusion containing the main findings and recommendations.